The management of patients with stable coronary syndromes - Commerford, Patrick (SA Heart Journal, 2017)
In coronary artery disease, symptoms and prognosis are not closely linked and sudden unexpected death or devastating acute myocardial infarction may be the first manifestation. In treating patients with stable coronary disease, we wish to both relieve symptoms and prevent adverse outcomes. Percutaneous revascularization provides excellent symptom relief but has no positive prognostic benefit in patients with stable coronary disease. The lesion causing the angina, treated by a stent, is not necessarily the lesion determining prognosis. Simple lifestyle modification and drug therapy are important determinants of prognosis. Coronary bypass graft surgery improves prognosis in well-defined subsets of patients and the application of percutaneous interventions in patients who might be better served by surgery can be questioned. It can be argued that the emphasis placed on percutaneous intervention in patients with stable disease may have adverse consequences.